Fostering pupils’ critical health literacy: examining the potential of physical education in lower secondary school - Haugen, Anders L. Hage; Riiser, Kirsti; Esser-Noethlichs, Marc; Hatlevik, Ove Edvard (Frontiers in Sports and Active Living, 2023)
Background In Norway, the introduction of an interdisciplinary subject named Public Health and Life skills has brought about renewed attention to how health is conceptualized and taught within and across school subjects. Physical education (PE) is one subject that has traditionally been linked to health outcomes. However, a narrow focus on increased physical activity as the main outcome of PE could be counterproductive in the pursuit of health. Critical health literacy (CHL) is put forward as a resource for health that can be nurtured in the PE context; this study hypothesizes that academic achievement in PE is positively associated with some aspects of CHL. Methods This cross-sectional study included 521 pupils aged 13–15 years old from five lower secondary schools in Norway. Structural equation models were used as the primary statistical analysis to test the hypothesis. The study controlled for parents’ education, leisure physical activity, and participation in sports club activities. Results The results confirm the hypothesis, showing a positive and significant association between PE and CHL. The association remains when controlling for parents’ education, leisure physical activity, and participation in sports club activities (βPECHL-C1 = 0.264, p = 0.001; βPECHL-C2 = 0.351, p < 0.000). Conclusion In our sample, academic achievement in PE was associated with higher levels of CHL. This study contributes to the ongoing discussion on the health benefits of PE. We argue that a resource-based health perspective can produce the appropriate aims for health in PE contexts and that the CHL concept contributes to illuminating key areas, promoting suitable teaching strategies, and bringing balance between an individual and collective focus for future health education, both within PE and across different subjects in school contexts.